Filtration behaviors in microfiltration with cyclic backwashing of sewage secondary effluent under constant rate and constant pressure conditions - Jami, Mohammed Saedi; Ohn, Than; Iritani, Eiji (The Society of Chemical Engineers Japan, 2004)
The performance of microfiltration with cyclic backwashing of secondary effluent emanating from a sewage treatment plant was assessed for the purpose of recycling of water. Microfiltration experiments were conducted under constant rate and constant pressure conditions, and filtration behavior in the two operations was compared. The filtrate obtained was found to be free from E. coli, and hence it can be reused as reclaimed water for urban reuse. As filtration proceeded, cake formation and pore blocking of the membrane occurred, causing an increase in pressure in constant rate filtration or flux decline in constant pressure filtration. Although backwashing was effective in decreasing cake resistance, the irreversible pore blocking of the membrane became gradually more severe with the increase in the number of backwashings. Characteristics of cake formation were analyzed using the compressible cake filtration model, and the pore blocking was found to be well described by a two-phase intermediate blocking law. As a result, the filtration behavior in constant pressure filtration with cyclic backwashing was expressed well by using models that represent cake formation and pore blocking, on the basis of the experimental data of constant rate filtration with cyclic backwashing. Moreover, it was shown from the experimental and predicted results that constant pressure filtration with cyclic backwashing assures almost constant throughput rate.